Different mechanisms of CDK5 and CDK2 activation as revealed by CDK5/p25 and CDK2/cyclin A dynamics - Otyepka, Michal; Bártová, Iveta; Kříž, Zdeněk; Koča, Jaroslav (The Journal of biological chemistry, 2006)
A detailed analysis is presented of the dynamics of human CDK5 in complexes with the protein activator p25 and the purine-like inhibitor roscovitine. These and other findings related to the activation of CDK5 are critically reviewed from a molecular perspective. In addition, the results obtained on the behavior of CDK5 are compared with data on CDK2 to assess the differences and similarities between the two kinases in terms of (i) roscovitine binding, (ii) regulatory subunit association, (iii) conformational changes in the T-loop following CDK/regulatory subunit complex formation, and (iv) specificity in CDK/regulatory subunit recognition. An energy decomposition analysis, used for these purposes, revealed why the binding of p25 alone is sufficient to stabilize the extended active T-loop conformation of CDK5, whereas the equivalent conformational change in CDK2 requires both the binding of cyclin A and phosphorylation of the Thr(160) residue. The interaction energy of the CDK5 T-loop with p25 is about 26 kcal.mol(-1) greater than that of the CDK2 T-loop with cyclin A. The binding pattern between CDK5 and p25 was compared with that of CDK2/cyclin A to find specific regions involved in CDK/regulatory subunit recognition. The analyses performed revealed that the alphaNT-helix of cyclin A interacts with the alpha6-alpha7 loop and the alpha7 helix of CDK2, but these regions do not interact in the CDK5/p25 complex. Further differences between the CDK5/p25 and CDK2/cyclin A systems studied are discussed with respect to their specific functionality.
Keywords: financování organizované; cyklin-dependentní kinasa 5; molekulární konformace; vodíková vazba; inhibitory proteinkinas; Protein Structure, Tertiary; threonin; Substrate Specificity; cyklin A; puriny; terciární struktura proteinů; Tyrosine; lidé; Stereoisomerism; stereoizomerie; Molecular Conformation; proteiny nervové tkáně; Phosphorylation; Models, Molecular; chemické modely; Phylogeny; Financing, Organized; cyklin-dependentní kinasa 2; Cell Cycle Proteins; Protein Conformation; Protein Structure, Secondary; molekulární modely; Nerve Tissue Proteins; fosforylace; Protein Kinase Inhibitors; Purines; sekundární struktura proteinů; Hydrogen Bonding; konformace proteinů; tyrosin; Models, Chemical; Threonine; Cyclin A; Cyclin-Dependent Kinase 2; substrátová specifita; fylogeneze; proteiny buněčného cyklu; Cyclin-Dependent Kinase 5; Humans